2024
DOI: 10.3390/life14040425
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Complexities of Oxidative Stress and Inflammation Biomarkers in Obstructive Sleep Apnea Syndrome: A Comprehensive Review

Salvatore Lavalle,
Edoardo Masiello,
Giannicola Iannella
et al.

Abstract: Background: Obstructive sleep apnea syndrome (OSAS), affecting approximately 1 billion adults globally, is characterized by recurrent airway obstruction during sleep, leading to oxygen desaturation, elevated carbon dioxide levels, and disrupted sleep architecture. OSAS significantly impacts quality of life and is associated with increased morbidity and mortality, particularly in the cardiovascular and cognitive domains. The cyclic pattern of intermittent hypoxia in OSAS triggers oxidative stress, contributing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 116 publications
0
1
0
Order By: Relevance
“…In addition, in hypertensive patients with moderate to severe OSAS, this central role played by intermittent hypoxia in the occurrence of low-grade inflammation could be explained by the fact that unlike hypopnoeas associated with micro-arousals, only hypopnoeas associated with oxygen desaturation appear to be involved in the development of cardiovascular risk factors [63]. Pathophysiologically, this occurrence of low-grade inflammation associated only with obstructive respiratory events inducing intermittent hypoxia may explain the activation of several deleterious mechanisms (induction of oxidative stress, reactive oxygen species production, activation of critical proinflammatory transcription factors, elevated expression of proinflammatory cytokines and chemokines, recruitment and infiltration of proinflammatory M1 macrophages) favouring inadequate activation of the inflammatory cascade [16,17,64]. Thus, in this study, we demonstrated the existence of a particular subtype of hypertensive patients at high cardiovascular risk characterised by the presence of low-grade inflammation induced by high intermittent hypoxia related to moderate to severe OSAS, which justifies systematic screening for this pathology in hypertensive patients with low-grade inflammation [65].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in hypertensive patients with moderate to severe OSAS, this central role played by intermittent hypoxia in the occurrence of low-grade inflammation could be explained by the fact that unlike hypopnoeas associated with micro-arousals, only hypopnoeas associated with oxygen desaturation appear to be involved in the development of cardiovascular risk factors [63]. Pathophysiologically, this occurrence of low-grade inflammation associated only with obstructive respiratory events inducing intermittent hypoxia may explain the activation of several deleterious mechanisms (induction of oxidative stress, reactive oxygen species production, activation of critical proinflammatory transcription factors, elevated expression of proinflammatory cytokines and chemokines, recruitment and infiltration of proinflammatory M1 macrophages) favouring inadequate activation of the inflammatory cascade [16,17,64]. Thus, in this study, we demonstrated the existence of a particular subtype of hypertensive patients at high cardiovascular risk characterised by the presence of low-grade inflammation induced by high intermittent hypoxia related to moderate to severe OSAS, which justifies systematic screening for this pathology in hypertensive patients with low-grade inflammation [65].…”
Section: Discussionmentioning
confidence: 99%
“…Malocclusion, which can be brought on by these changes in tooth position, may contribute to the onset or worsening of OSA [83]. Furthermore, continuous positive airway pressure (CPAP) therapy should be considered when managing OSA over the long term [84]. Dental adverse effects from CPAP have been linked to modifications in occlusal relationships and bites.…”
Section: Palatal and Dental Changesmentioning
confidence: 99%